Synthesis of oolongtheanins and their inhibitory activity on micellar cholesterol solubility in vitro. Issue 4 (15th February 2015) - Ogawa, Kazuki; Hirose, Sayumi; Yamamoto, Hitomi; Shimada, Masaya; Nagaoka, Satoshi; Yanase, Emiko
Graphical abstract